2010
DOI: 10.1109/tap.2010.2078449
|View full text |Cite
|
Sign up to set email alerts
|

Miniaturized Substrate Integrated Waveguide Slot Antennas Based on Negative Order Resonance

Abstract: Miniaturized waveguide slot antennas using negative order resonance are proposed and developed in this paper. The design of these novel resonant-type antennas is based on the study of a composite right/left-handed (CRLH) substrate integrated waveguide (SIW) starting from the dispersion diagram and the equivalent circuit. These proposed CRLH resonators are realized by etching the interdigital slot on the surface of the SIW. The slot acts as a series capacitor as well as a radiator leading to a CRLH antenna appl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
74
0
5

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 153 publications
(82 citation statements)
references
References 34 publications
0
74
0
5
Order By: Relevance
“…It is observed that the measured results are agree with the simulated ones. Table 1 for the fabricated and reported NOR antennas with the measured NOR frequency, the antenna's electrical size and the measured peak gain [12,13]. From this Table, the electrical sizes of the fabricated open-ended and short-ended antennas are 75.8% and 74.6% smaller than those of the reported counterparts, respectively.…”
Section: Nor Antennas Designmentioning
confidence: 92%
See 3 more Smart Citations
“…It is observed that the measured results are agree with the simulated ones. Table 1 for the fabricated and reported NOR antennas with the measured NOR frequency, the antenna's electrical size and the measured peak gain [12,13]. From this Table, the electrical sizes of the fabricated open-ended and short-ended antennas are 75.8% and 74.6% smaller than those of the reported counterparts, respectively.…”
Section: Nor Antennas Designmentioning
confidence: 92%
“…The equivalent circuit with all the extracted values describes the dispersion relation of the proposed unit-cell very well. Since a longer and thinner Hilbert-fractal slot with more corners provides a larger series capacitance, the proposed unit-cell has a much smaller physical size even with the same lefthanded band (below 8.2 GHz) by comparing with the unit-cell reported in [12,13]. Therefore, the fractal-based CRLH TL can be used to design miniaturized NOR antennas.…”
Section: Fractal-based Crlh Tl Realization and Dispersion Analysismentioning
confidence: 93%
See 2 more Smart Citations
“…This technology is produced on a planar substrate with linear periodic arrays of metallic vias based on the printed circuit board (PCB). A structural sample along with required relation, in which SIW technology is used, is shown in Figure 1 [3][4][5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%